In vivo Imaging of a Novel Strain of Bacteroides fragilis via Metabolic Labeling - Xu, Wenye; Su, Peizhu; Zheng, Lijun; Fan, Hongying; Wang, Ye; Liu, Yangyang; Lin, Yuqing; Zhi, Fachao (Frontiers in Microbiology, 2018)
Non-toxic Bacteroides fragilis(B. fragilis) is regarded as a potential candidate for probiotic owing to its multiple benefits. We previously isolated a new strain of B. fragilis (ZY-312) and also verified its biosafety and capability of inhibiting pathogens in vivo. However, whether and where ZY-312 colonizes in the gastrointestinal(GI) tract remains to be determined. To track the colonizaiton of ZY-312, mice were gavaged with ZY-312 labeled by means of metabolic oligosaccharide engineering and bioorthogonal click chemistry or given AF647-dibenzocyclooctyne（DIBO） directly. Then the fluorescence was detected in GI tract, spleen and kidneys. Results showed that ZY-312 could be labeled by metabolic oligosaccharide engineering, and the optimal incubation time with AF647-DIBO was 5h in vitro. Following oral gavage with AF647-DIBO labeled ZY-312 or AF647-DIBO alone, mice were subjected to in vivo imaging and results demonstrated that the fluorescence intensity seemed similar in both groups at 3h, 6h and 12h. Notably, while the fluorescence of AF647-DIBO disappeared at 24h probably due to excretion via GI tract, that of AF647-DIBO labeled ZY-312 retained in the cecum as long as 48h. Immunofluorescence assay further confirmed that labeled ZY-312 colonized not only in the cecum but also in the stomach, ileum and colon in mice 48h post-gavage and that no massive accumulation of ZY-312 was detected in other organs including kidneys and spleen. In conclusion, ZY-312 could colonize in the GI tract, mainly in cecum, for at least 48 hours, and it hardly disseminate to other organs as well, shedding new light on the future development of B. fragilis as a probiotic product.